2009
DOI: 10.3233/jad-2009-1162
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Enhanced Zinc on Spatial Memory and Plaque Formation in Transgenic Mice

Abstract: There is considerable evidence suggesting that metals play a central role in the pathogenesis of Alzheimer's disease. Reports suggest that elevated dietary metals may both precipitate and potentiate an Alzheimer's disease phenotype. Despite this, there remain few studies that have examined the behavioral consequences of elevated dietary metals in wild type and Alzheimer's disease animals. To further investigate this in the current study, two separate transgenic models of AD (Tg2576 and TgCRND8), together with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 30 publications
3
37
1
Order By: Relevance
“…Among many other factors, metal ions (e.g., Al, Cu, Fe, and Zn) have been shown to affect the pathways of Ab folding. The abnormal aggregation of Ab could stimulate astrocyte activation as well as oxidative stress events, which both result in impairment of neuronal functions Behavioral studies on transgenic mice examining the effect of Zn supplementation reported an increased impairment of spatial memory, but with a concomitant unexpected reduction of Ab deposits (Linkous et al 2009). In contrast, compounds affecting Zn homeostasis have been shown to decrease Ab brain deposition (Lee et al 2004;Adlard et al 2008).…”
Section: Zincmentioning
confidence: 97%
“…Among many other factors, metal ions (e.g., Al, Cu, Fe, and Zn) have been shown to affect the pathways of Ab folding. The abnormal aggregation of Ab could stimulate astrocyte activation as well as oxidative stress events, which both result in impairment of neuronal functions Behavioral studies on transgenic mice examining the effect of Zn supplementation reported an increased impairment of spatial memory, but with a concomitant unexpected reduction of Ab deposits (Linkous et al 2009). In contrast, compounds affecting Zn homeostasis have been shown to decrease Ab brain deposition (Lee et al 2004;Adlard et al 2008).…”
Section: Zincmentioning
confidence: 97%
“…The difference in magnitude can be explained by methodological differences; the former measured chelatable levels, whereas the latter measured total tissue zinc isotope contents. Moreover, diet and drinking water in rodents have been shown to influence brain zinc levels (32,33), making whole brain tissue analysis of trace metals from rodents more prone to variability in comparison with cultured cells where known amounts of trace metals are found in media or buffers. Nevertheless, we clearly established that abnormal Zn 2ϩ metabolism is present in MLIV cells.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, dietary zinc deficiency exacerbated behavioral and histological pathology in an APP mutant mouse (Stoltenberg et al 2007), and zinc supplementation prevented AD pathology in the 3X-Tg mouse model (Corona et al 2010). However, another study found impaired memory performance in zinc supplemented APP mutant mice associated with decreased Ab deposition (Linkous et al 2009). …”
Section: Therapies Aimed At Modulating Zinc Availabilitymentioning
confidence: 99%